The Effect of Social Media Platform in Simulation of Major Subjects Among Grade 12 Home Economic Students of Bestlink College of the Philippines: Vol.3, No.1D (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study focused on the effect of Social Media Platforms in the Simulation of a Major subject among Grade 12 home economics students. Social media is extremely important in the study of home economics students. They spend most of their time on social media as an integral part of their daily lives. We can define social media platforms as a wide range of things, such as messaging apps like Messenger, Facebook, and Instagram, and video portals like YouTube that students can use to gain information. Furthermore, simulating social media is very important for home economics students; they have opportunities to improve their self-esteem, self-confidence and self-awareness. Social media simulation teaches skills, knowledge, and competencies needed for a student to perform a specific job within the specialization they will need to practice through social media. Still, the school location found out that not all students have a reliable connection and stable environment to work. Some students can simulate this forum and demonstrate how we respond in real-life scenarios. Fifty (50) students from the population of all the home economics at Bestlink College of the Philippines during the school year 2021-2022 were selected using a purposive sampling technique based on the diagnostic test result. This study employed a descriptive qualitative method, simple percentage and weighted mean to determine the effect of social media platforms in a simulation of major subjects among grade 12 home economics students of Bestlink College of the Philippines.  Fifty (50) students from the population of all the home economics students were sampled in the study. The instrument used is a survey questionnaire distributed and done via Google Meet. This study revealed the effect of social media platforms in a simulation is that students are more likely to have self-directed learning and struggle under simulation due to a lack of gadgets that students can invest in to buy their gadgets. Thus, this study recommended that the student invest to buy a gadget for their simulation. Finally, a student must be more attentive to their online class to absorb learning better.
Keywords: Simulation; Social media platform; Major Subjects